E-COMMERCE EFFECT AND VALUE ADDED TAX (VAT) POLICY ON CONSUMER BEHAVIOR: (Study at the Faculty of Economics and Business, Muslim University of Indonesia) - Muhammad Fathur; Tenriwaru Tenriwaru; Muhammad Abduh (JOSAR (Journal of Students Academic Research), 2020)
This study aims to determine the effect of e-commerce and Value Added Tax (VAT) policy on consumer behavior. The data in this study were obtained from students of the Faculty of Economics and Business, Muslim University of Indonesia who were willing to become respondents. This study uses primary data by conducting direct research in the field by providing online questionnaires to 88 respondents. The research used is quantitative method; the type of data used in this research is primary data by distributing online questionnaires. The sample selection technique used purposive sampling. The method of data analysis of this research was carried out by using descriptive statistical tests, data quality testing, classical assumption tests and hypotheses using SPSS software. The results showed that the existence of e-commerce and VAT policies had a positive and significant effect on consumer behavior, because with the e-commerce, students of the Faculty of Economics and Business felt it was easier to buy the desired goods and students trusted e-commerce sites more if there was clear information about the imposition of VAT and considers that the VAT policy is something that does not harm or does not affect the desire to buy the product.